The Role of EGCG on the Expression of p38 MAPK, IL-6 and TNF-a Biomarker Proteins in the Cisplatin Induced Kidney Damage in Rats - Toprakoglu, Nuran; Aslan, Abdullah; Beyaz, Seda; Gok, Ozlem; Erman, Orhan; Tan, Fatih; Erman, Fazilet (Pleiades Publishing Inc, 2023)
a polyphenolic catechin, has anticancer, antiinflammatory and antioxidant effects on kidney tissue. It was aimed to determine the antiinflammatory, antioxidant effect of EGCG against cisplatininduced nephrotoxicity. 28 male Wistar albino (n = 28, 8 weeks old) rats were used. Rats were divided into 4 groups and each group included 7 rats. The groups were: (i) Control Group: fed with a standard diet; (ii) EGCG Group: Standard diet + EGCG; (iii) Cis Group: Standard diet + Cis; (iv) Cis + EGCG Group: They were fed with standard diet + Cis + EGCG. In the EGCG-treated group (Cis + EGCG), the expression levels of p38a MAPK, IL-6 and TNF-a proteins, which are inflammation markers, were found to be significantly decreased compared to the Cis group (p < 0.05). Our results show that cisplatin increases MDA levels from antioxidant defense systems, decreases glutathione (GSH) and catalase (CAT) activity, thus activating oxidative metabolism and causing damage. In the histopathological examination, it was observed that kidney damage occurred significantly in the cisplatin-administered group, whereas it decreased in the EGCGadministered group. These results show that EGCG treatment has an antiinflammatory effect and it can significantly prevent nephrotoxicity.
Keywords: apoptosis; EGCG; IL-6; p38 MAPK; TNF-& alpha;